Letter to Jane Tolmach from Chuck Winner - Chuck Winner:::::: (1966)
A letter from the Committee to Re-Elect Governor Brown, Chuck Winner writes to Jane Tolmach praising a recent meeting she organized, calling it one of the best the Brown staff had attended. He notes that he failed to obtain a list of attendees and the organizations they represented. Winner asks her to send a list of participants so he can forward registration materials and additional information.